Herbigation in a Vineyard: Efficacy and Persistence of Five Pre-emergence Herbicides in a Sandy Soil - Fourie, J.C. (South African Journal of Enology and Viticulture, 2017)
The persistence of simazine, oxadiazon, napropamide, oryzalin and acetochlor in a sandy soil was monitored over a period of 60 days by means of a bio-assay. Sixty days after application 3% of simazine, 5% of acetochlor, 6% of oxadiazon, 53% of oryzalin, and 54% ofnapropamide, initially present, were detected in the 0-300 mm soil layer. Simazine, oxadiazon, acetochlor and napropamide leached. Oryzalin was resistant to leaching and showed the highest efficacy and therefore is the most suitable for use on sandy soils. The herbicides were more efficacious when applied in a 5 mm herbigation than in a 16 mm herbigation. The criteria established for herbigation on a sandy soil could be used as a guideline for light-textured soils.